Características citológicas de cistoadenocarcinoma papilar ovariano em um cão - Antunes, Tamires Ramborger; Peixoto, Renata Amarilha Valençoela; Matsuda, Raquel Mineko; de Oliveira, Gustavo Gomes; da Silveira, Alessandra Welzel; Godoy, Kelly Cristina da Silva; dos Santos, Ariany Carvalho; de Souza, Alda Izabel (Acta Scientiae Veterinariae, 2017)
Background: Ovarian papillary cystadenocarcinoma is a rare neoplasm associated with peritoneal implantation and malignant effusion. Most dogs are asymptomatic until the nodules become large and the abdominal volume is increased. From the clinical suspicion, the diagnosis can be obtained through imaging and histopathology, however, cytological analysis has become an alternative method for the early detection of this neoplasm. In order to demonstrate the importance of cytology in the diagnosis of ovarian neoplasms and its metastasis, it is reported a case of metastatic ovarian papillary cystadenocarcinoma in a dog. Case: Female, intact, teckel, 5-year-old, with increased abdominal volume. Physical examination revealed ascites and intracavitary mass, abdominocentesis and fine needle puncture of the mass were performed for cytological evaluation. In the cavity fluid it was observed: dark red color, cloudy appearance, hematocrit of 35%; (7.6 g / dL), pH (8.0), 22,000 nucleated cells / μL, marked cellularity of pleomorphic epithelial cells arranged in three-dimensional cohesive groups, sometimes in acinar or tubular pattern, nucleus with loose chromatin coarse, scarse to moderate cytoplasm, perinuclear halo, multiple and evident nucleoli compatible with carcinomatous neoplastic effusion. In the cytological evaluation of the tumor, epithelial cells were observed, with the same microscopic characteristics of the abdominal fluid. A laparotomy that did not show metastasis was performed, multiple nodes interspersed with cystic regions containing yellow-red fluid in the right ovary were visualized. Histopathology showed: neoplastic cells proliferation of ovarian glandular tissue, scarce cytoplasm, poorly delimited, nucleus ranging from oval to cylindrical with marked pleomorphism, evident nucleoli and loose chromatin, mitotic figures and papillary growth. Neoplastic cells forming irregular cavities with proteinaceous fluid, scarce connective tissue intermingling the cellular nest and areas of hemorrhage. Cytological and histopathological analyzes were compatible with ovarian papillary cystadenocarcinoma. After three months of excision, the dog returned with thoracic effusion that presented the same characteristics of the abdominal fluid, indicating metastasis. Discussion: Metastasis and effusion were observed in 48% and 86% of dogs with this tumor, respectively. Cell exfoliation, release of fluid through the tumor capsule or rupture of cysts can result in transcelomic metastatic implants that exert pressure and obstruct peritoneal and diaphragmatic lymphatic vessels causing effusion. The macro and microscopic characteristics of the abdominal effusion reinforced the suspicion of neoplasia, and the cytomorphological evaluation of the tumor, which identified carcinomatous cells similar to that of the effusion, allowed the presumptive diagnosis of the neoplasia. The macroscopic presence of multiple nodes interspersed with cystic regions containing red fluid in the right ovary, identified after surgical excision, reinforced the cytologic diagnosis. Histopathological examination identified wellestablished microscopic features that allowed the definitive and confirmatory diagnosis of neoplasia. Radiological analysis of the chest was not enough to detect the metastasis diagnosed by effusion analysis, however, small nodules (less than 6 mm) are difficult to identify by imaging. Thus, it is important to emphasize the importance of cytological evaluation of tumor and effusions for detection of neoplastic cells for the diagnosis of intracavitary neoplasia and metastasis.